Governing invasive plants: Policy and practice in managing the Gamba grass (Andropogon gayanus) – Bushfire nexus in northern Australia. (September 2015) - Head, Lesley; Atchison, Jennifer
Highlights: We examine invasive plant Gamba grass ( Andropogon gayanus ) governance practice in Australia. Qualitative analysis reveals how Gamba exceeds governance and absolute control. The Gamba-fire assemblage mobilises resources but not in a way that is consistent with best weed practice. Attention to practice provides opportunities for more effective on ground action. Living with invasive plants should be part of the governance framework. Abstract: Predicted nonlinear changes in the Anthropocene will challenge the extent to which environmental issues are governable. Climate change projections highlight positive feedbacks between invasive species spread and increased bushfire risk. We use empirical evidence of current practices of invasive plant management, and the case of Gamba grass ( Andropogon gayanus ), to illustrate what it means to live with invasive plants. Gamba is a significant threat to tropical savanna biodiversity through its influence on fire regimes across northern Australia. We analyse the practices of Gamba governance via policy analysis, interviews with over 50 managers and participant observation. Our results show the multiple ways in which Gamba exceeds and escapes governance, exposing the impossibility and risks of absolute control as a management framing. By attending to practice in this way, we show how an alternative framing, in which living with weeds is a more explicit part of the governance framework, can work. Our framing contributes to more effective management because political choices are made more transparent, valorises pragmatic knowledge about the messy reality of living with weeds, and mobilises a broader range of resources including land managers now resistant to the state. The Gamba-fire assemblage has mobilised political action by invoking fire policy rather than weed policy, but not necessarily in a way consistent with best practice weed management. Attention to these practices of vernacular governance not only shows the ideal of present control to be illusory, but will also provide important cultural resources in the form of networks and capacity, as the challenges of invasive species shift and intensify.